Ekspressiv skriving som egenterapeutisk verktøy ett år etter brystkreftdiagnosen - resultater fra en norsk pilotstudie - Birgitta Haga Gripsrud; Håvard Søiland; Kirsten Lode (Septentrio Academic Publishing, 2015)
Expressive writing as a self-help tool one year after the breast cancer diagnosis - results from a Norwegian pilot study The article presents findings from a pilot study on expressive writing, a therapeutic method undescribed in a Norwegian scientific context. Objective: 1. Gain qualitative data on breast cancer women's experiences with expressive writing. 2. Evaluate the intervention's feasibility, based on participants' experiences of the instruction, procedure, and circumstances for writing. Method & design: The study has an exploratory descriptive design. Data collection was achieved through in-depth interviews, followed by experiential thematic analysis of transcripts. Results: Two women enrolled, participating in writing/interviews. Analysis revealed three themes: "The experience of the writing process", "Writing as working through and work to clear the mind", "Strength and vulnerability in relation to others". Conclusion: Findings reveal that expressive writing was experienced as achievable for two breast cancer women, one year after diagnosis. Writing provided an opportunity to work through, and sort out, feelings and thoughts connected to participants' lives and illness experiences. The instruction was evaluated as easy to understand and inspiring. The women became absorbed in electronic writing in their own homes. They both recommended expressive writing for other women with breast cancer, especially in the period after initial diagnosis.